Quantification and characterization of atmospheric microplastics in a coastal urban area of the city of Lima, Perú - Palomino López, Jhomara (2024)
Microplastics are currently considered an emerging problem. That are mainly associated with the excessive use and poor disposal of plastic waste, a problem that has worsened worldwide in recent decades. Studies on the presence of microplastics are limited due to the lack of knowledge on their behaviour and incidence in ecosystems, especially in the atmosphere, and on their consequences on human health. We were conducted a study in a coastal urban area of the city of Lima-Peru, with the main of quantifying the presence of atmospheric microplastics and identifying their morphological characteristics such as shape, size and colour. The result obtained was in the presence of 1598 microplastic particles (in 30 days of monitoring), 68% were fragment type, 22% fiber type and 10% sphere type. The predominant colours were blue and green, and the average size found ranged from 2.495-216 μm. Meteorological conditions were also considered in relation to contaminant deposition. The study is one of the first carried out in Peru, so it is expected that the information generated will be useful to obtain more knowledge about this new pollutant.